Kekerasan Mental (Bullying) sebagai Isu Kesehatan Masyarakat di Indonesia - Satria Yudistira; Helmy Astiza Rut Hanani (VISA: Journal of Vision and Ideas, 2024)
Bullying comes from the word "bully" which means bully, and this behavior can cause physical and psychological pressure on the victim. Psychological impacts include depression, anxiety, social isolation, low self-esteem, and even suicide, while physical symptoms include stomach aches, headaches, and difficulty sleeping. Bullying cases in Indonesia have increased significantly, causing serious impacts on teenagers' mental health such as depression, stress and the risk of suicide. Factors that cause bullying include peers, use of social media, and parenting patterns in the family, as well as the child's individual personality. Library research is a method for collecting information from previous studies without having to use primary or secondary data. This study involves collecting data from books, literature, notes, and reports that are relevant to the problem under study. Literature research emphasizes philosophical and theoretical discussions rather than empirical testing in the field. The results of this research reveal that bullying is aggressive behavior that is carried out repeatedly to hurt or intimidate other people in an unequal power relationship. Types of bullying include physical, verbal, cyberbullying, non-verbal, and relational. Physical bullying involves direct violence such as hitting, while verbal bullying involves insults and threats. Cyberbullying uses digital technology to spread messages that demean victims. Non-verbal bullying includes actions such as derogatory body language, while relational bullying involves the manipulation of social relationships. Research shows that bullying has a significant impact on the mental and emotional well-being of victims, causing stress, depression, anxiety and even suicide.